Level of Understanding of Paud Teachers About Stunting Mitigation in PAUD Units of Preschool Talaud Islands Regency North Sulawesi Province - Saune, Deice; Puridawaty, Brigita (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This study aims to determine the level of understanding of PAUD teachers about stunting mitigation in PAUD Units in Talaud Islands Regency, North Sulawesi Province. The researcher used a survey method by distributing questionnaires to PAUD teachers in Talaud Regency. With a sample of 35 teachers, the results showed that the level of understanding of PAUD teachers about stunting mitigation in PAUD Units in Talaud Islands Regency, North Sulawesi Province was "Medium" at 49.33% (37 teachers), "Low" at 36% (27 teachers), and "High" at 14.67% (11 teachers). Based on the average value, which is 3.28%, the level of understanding of PAUD Units about the Implementation of Stunting Mitigation in Talaud Islands Regency is in the "MEDIUM" category.